2010
DOI: 10.3109/02656730903417947
|View full text |Cite
|
Sign up to set email alerts
|

Severe, short-duration (0–3 min) heat shocks (50–52°C) inhibit the repair of DNA damage

Abstract: Severe (50 degrees C) short-duration (15 s or greater) heat shocks inhibit repair of UV-induced DNA damage. The ability to detect the inhibitory effects of very short, 15-60 s, heat shocks was assay dependent. The comet assay could detect repair inhibition after a 15-s heat shock. Detection of DNA damage by specific antibodies could only detect repair inhibition after 1-3-min heat shocks. Using the gamma-H2AX foci method 30 s at 50 degrees C induced a significant delay in the repair of DNA damage after 1 Gy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…2c) are shown. The γH2AX foci and the γH2AX uorescence intensity increased under all procedures in the thermal controls showing that heating the HeLa cells by 5 ºC induces DSBs and inhibits their repair, which is consistent with previous reports 14,15 .…”
supporting
confidence: 92%
“…2c) are shown. The γH2AX foci and the γH2AX uorescence intensity increased under all procedures in the thermal controls showing that heating the HeLa cells by 5 ºC induces DSBs and inhibits their repair, which is consistent with previous reports 14,15 .…”
supporting
confidence: 92%
“…Further, heat-induced HSP70 expression varies significantly with cell types [60,61,62,63,64]. Heat shocks (45 °C) for a brief period (10 -30 min) were reported to cause cell death [7,17]. However, when the cells were allowed to recover at 37 °C, the cells experienced more senescence than the loss of cell viability [7,65].…”
Section: Hyperthermia Causes G1 Arrest and Triggers Both Senescence Amentioning
confidence: 99%
“…Though human body temperature limits within 40 °C during heat stroke or fever, most of the studies reported the cellular effects of hyperthermia at 42 to 47 °C [7,17] Importantly, the human body is subjected to prolonged heat during summers and adverse working conditions; therefore, the cellular effects of the prolonged hyperthermia at a physiologically relevant temperature (40 °C) need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The THz power density must not be too high to avoid detrimental thermal effects on the sample. Many studies have shown the effect of heating on cells, such as tissue damage [ 23 , 24 ], heat-induced cellular death [ 25 , 26 ], and DNA damage [ 27 , 28 ]. Thus, the THz beam should not be focused tightly to prevent an increase in the temperature on the sample.…”
Section: Introductionmentioning
confidence: 99%